ANALISIS SWOT SEBAGAI LANDASAN DALAM MENENTUKAN STRATEGI PEMASARAN ( STUDI KASUS McDONALD’S RING ROAD) - Ahmad Ramadhan; Fivi Rahmatus Sofiyah (Jurnal Media Informasi Manajemen, 2013)
ABSTRACT This research aims to identify and analyze the marketing strategy of McDoanald’s Ring Road by using the SWOT analysis consisting of Strength, Weakness, Opportunities and Threats as a strategy to improve the competitiveness of McDonald’s Ring Road This research is a descriptive research using matrix analysis IFE (Internal Factor Evaluation), EFE (External Factor Evaluation), and the SWOT Matrix. To obtain the accurate data, the methods used are interviews (in-depth interviews), and test of methods triangulation. Several alternative strategies will be selected using QSP Matrix. The result of this research in that McDonald’s Ring Road has strength, weakness, oppurnities, and threats in marketing activities. The result of QSP matrix analysis in that McDonald’s Ring Road must use the first altenative strategy which making corporation with Coca-cola to interested the consumer of Coca-cola Keywords: Strengths, Weaknesses, Opportunities, Threats